The origins and restriction of efficiency in public administration: Regaining efficiency as the core value of public administration - Rutgers, Mark R.; van der Meer, Hendriekje (2010)
This article is primarily a study in the history of the concept of efficiency. It is argued that efficiency originated in Aristotelian ideas about causality and acquired a broad, substantive meaning of "moving force." This meaning of the term was dominant well into 20th-century studies of public administration. In the course of the 20th century, however, efficiency became predominantly understood as "technical efficiency": a ratio between resources and results. This connotation is especially clear in the explicit "textbook" definitions of efficiency. Nevertheless, we claim that the substantive meaning of efficiency is still around, and even at the heart of much criticism of efficiency. Technical efficiency obscures that efficiency in public administration is to be assessed in the light of public values. Efficiency as signifying the necessity of having capable operative administrative agents constitutes one of the, if not the, core value of the field. -- Reproduced.
Keywords: Public administration